KLAUSULA BAKU PERJANJIAN KREDIT ANEKA GUNA BANK RIAU KEPRI DITINJAU DARI UNDANG-UNDANG NO. 8 TAHUN 1999 - Martha Hasanah Rustam (Riau Law Journal, 2018)
According to law number 8 of 1999 on Consumer Protection, raw clause is any rules or terms and conditions have been prepared in advance and set unilaterally by businessmen who poured in a documents and binding agreement/and must be filled by the consumer. Because the raw clause used in the credit agreements are unilateral where the bank that determines the content of the clause while the customer had no choice to change it because of the position of the customer in a weak position. This Research method using normative. From this research it can be concluded that there is a position that is not balanced between the banks as creditors with the customer as debtor and Credit Agreement Assorted raw clause in order to Bank Riau Kepri still contrary to the provisions of article 18 law number 8 of 1999 on Consumer protection.Keywords : The Raw Clause, Bank Credit Agreement